The effectiveness of the use of the Android-based Carom games comic integrated to discovery learning in improving critical thinking and mathematical representation abilities - Mega Septiana Ika Rahayu; Heru Kuswanto (OmniaScience, 2021)
This research aims to reveal the effectiveness of the use of the Android-based carom games comic integrated to discovery learning (MIKIMOM) in improving critical thinking and mathematical representation in the teaching of physics. It is quantitative research with the   quasi experimental research design. It was conducted in two phases, with the first phase for empirical try out of the test and second phase for the application of MIKIMOM to reveal the effectiveness of the developed media in teaching. The empirical try out was conducted to 261 grade XI MIA students, while the application of the media was conducted to 32 grade X MIA students of State Senior High School (SSHS) 2 Banguntapan using the Power Points materials. The data were collected using a critical thinking and mathematical representation test which was valid and reliable according to the empirical testing. The data were analyzed using the QUEST program to see the validity and reliability of the test items, and the MANOVA test to see the effectiveness of the media. The research finding shows that MIKIMOM is effective in improving the critical thinking and mathematical representation of the students with the scores of 0.287 (large effect size) and 0.179 (medium effect size).